2023
DOI: 10.1097/tp.0000000000004537
|View full text |Cite
|
Sign up to set email alerts
|

Novel Endpoints in Solid Organ Transplantation: Targeting Patient-reported Outcome Measures

Abstract: Although solid organ transplantation improves survival and quality of life in many patients with organ failure, treatment complications and side effects can have debilitating consequences for patients. Patient-reported outcome measures (PROMs) capture how patients feel and function, including quality of life, symptoms, and side effects that are assessed directly by patients. Yet, they remain infrequently reported in trials in solid organ transplantation. Barriers to implementing PROMs in trials include uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The nature of LT, encompassing the patient’s journey from the time of registration on the waiting list to long-term post-transplant survival, highlights the need for longitudinal health related quality of life data [ 43 ]. However, most studies reported to date are most often cross-sectional analyses and pay little attention to the phase post-transplant [ 27 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The nature of LT, encompassing the patient’s journey from the time of registration on the waiting list to long-term post-transplant survival, highlights the need for longitudinal health related quality of life data [ 43 ]. However, most studies reported to date are most often cross-sectional analyses and pay little attention to the phase post-transplant [ 27 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…All stakeholders including solid organ transplant candidates and recipients, transplant professionals, and researchers in the field of transplantation strongly supported that a core outcome set be defined to facilitate comparative studies and give impetus to the field. A core outcomes set refers to a minimum set of outcome measures that are critical to patients, caregivers, and health professionals for decision making [71]. Selected outcomes that have so far not been considered but do carry clinical relevance during the pretransplant waiting time are health-related physical fitness parameters such as muscular fitness, motor fitness, body composition and (cardio)metabolic health, as well as patientreported outcomes such as fatigue, medication adherence and lifestyle, and clinical outcomes such as duration of intensive care stay, hospitalization, (re-)admissions, complications, graft function and survival, and waitlist and post-transplant mortality.…”
Section: Recommendation 31mentioning
confidence: 99%